Energy Evolution and Acoustic Emission Characteristics of Uniaxial Compression Failure of Anchored Layered Sandstone - Yu, Yang; Zhao, Da-Cheng; Feng, Guang-Liang; Geng, Da-Xin; Guo, Hao-Sen (Frontiers in Earth Science, 2022)
To study the energy evolution and acoustic emission characteristics of layered sandstone under anchorage in the process of deformation and failure, the sandstone samples from Chuxiong Yi Autonomous Prefecture, Yunnan Province were selected for uniaxial compression testing. The energy evolution in the process of sandstone failure and the spatial fractal characteristics of acoustic emission events in the process of deformation and failure were investigated. Research results show that anchoring can make layered sandstone store more energy, the stored energy first increases, then decreases with the increase of bedding angle, 45°-anchored sandstone stores the most energy; in the plastic stage, acoustic emission of layered sandstone shows an active period, accompanied by high AE event counts and high energy, and the duration of the active period increases under the action of anchorage; the B value of sandstone under anchorage is generally higher than that of unanchored sandstone in the whole deformation and failure process, and the continuous decline in B value can be used to indicate a precursor to instability and failure; under the action of anchoring, the D value of sandstone (its fractal dimension) also increases, then decreases with the increase of bedding angle. The D value changes within [2,3]. At a given bedding angle, the D value of anchored sandstone is greater than that of unanchored sandstone, the D value of 30° anchored sandstone increased the most (by 12.33%); the maximum D value occurred in 45° anchored sandstone (reaching 2.72) and the spatial distribution of acoustic emission events and damage of sandstone under anchorage is also more uniform; under increasing stress, the number of acoustic emission events is less widely distributed in the early stage and more densely distributed in the later stage. The growth rate of the D value varies across different peak stress ranges, which is more significant under the action of anchorage. The acoustic emission event counts grow evenly and slowly in the space, and the toughness of sandstone is improved to a certain extent under the action of anchorage.